Imaging of Adverse Reactions to Metal Debris - Maloney, Ezekiel; Ha, Alice S.; Miller, Theodore T. (Seminars in Musculoskeletal Radiology, 2015)
Hip replacements with metal-on-metal components can cause a spectrum of adverse tissue reactions—from benign localized fibrosis and chronic inflammation to delayed hypersensitivity response. In addition to history, physical examination, and relevant laboratory data, imaging plays a critical role in the evaluation of hip arthroplasties. Imaging assessment begins with radiographs and may be followed by ultrasound, computed tomography, or MRI. MRI optimized for metal artifact reduction is the most sensitive and specific imaging modality and is essential in assessing the spectrum of metal-related adverse tissue reactions. In this article, we discuss the history, pathophysiology, and imaging findings of adverse reactions to metal debris.
Keywords: metallosis; ARMD (adverse reactions to metal debris); hip arthroplasty; imaging